(untitled) (Research, Society and Development, 2021)
The debate about the increase in cases of people infected by the new coronavirus and its relationship with the lack of public basic sanitation policies, has raised questions from the academic community to scientists studying this problem. The objective of this article is to analyze the relationship between the incidence of cases of people infected with the new coronavirus from March 15 to June 30, 2020, with the lack of public basic sanitation policies in the capitals of the southern and northern regions of Brazil. . The research is classified as bibliographic, descriptive, and exploratory in nature, carried out by searching the IBGE database, and on the websites of the Health Secretariats of the Capitals of the North and South of Brazil and news portals. The method employed was qualitative and quantitative, in addition to content analysis. In the analysis it was found that, in cities that have the highest coverage of sewage collection and treated water supply, they had the lowest incidence rates of people infected by Convid-19 per (100 thousand inhabitants).